On the sedimentation modeling by a hyperbolic equation and its degeneration - Kryvonos, Yu.G.; Selezov, I.T. (Reports of the National Academy of Sciences of Ukraine, 2014)
A generalized model of sedimentation, which considers the evolution of sediments on the bottom surface with a finite velocity is presented. We investigate a singular degeneration of the generalized hyperbolic equation to the traditional equation in the class of generalized solutions.